2012
DOI: 10.5455/ijmsph.2012.1.38-42
|View full text |Cite
|
Sign up to set email alerts
|

Study of psychological stress among undergraduate medical students of government medical college, Surat.

Abstract: Background: Psychological stress among medical students is common as compared to other professional courses. The prevalence of perceived stress among medical students affects not only their academic performances but also to some extent their health. Objective: The present study was undertaken to determine the prevalence of self-perceived psychological stress among UnderGraduate medical students, to identify probable factors responsible for it and to suggest possible interventions. Materials and Methods: A cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
3
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 10 publications
(17 reference statements)
3
37
3
3
Order By: Relevance
“…Study by Solankyet al found that 41.2% undergraduate student suffers from severe stress during the course of study. [7] Study by Nagajyothi et al also found similar level of stress. [8] Hence, we assumed that we would get similar level of stress among medical students.…”
Section: Methodssupporting
confidence: 48%
See 1 more Smart Citation
“…Study by Solankyet al found that 41.2% undergraduate student suffers from severe stress during the course of study. [7] Study by Nagajyothi et al also found similar level of stress. [8] Hence, we assumed that we would get similar level of stress among medical students.…”
Section: Methodssupporting
confidence: 48%
“…Study by Solanki et al showed that 55.6% students experience mild to moderate stress and the principal contributing factor for stress is examination. [7] Thakur et al…”
Section: Discussionmentioning
confidence: 99%
“…But in the study done in Lahore, Pakistan 24% of students reported lack of entertainment in the institution as an important (often/always) source of stress 17 . In a study done in Surat, India to identify the psychological stressors among medical students did not find any association of living status with level of stress 28 . Majority of our students were residing in the hostels provided in the campus.…”
Section: Discussionmentioning
confidence: 91%
“…Psychological stress among medical students is common as South American Journal of Academic Research Special Edition May 2016 2 compared to other professional courses. (Solanky, Desai, Kavishwar, & Kantharia, 2012;Kittu & Patil, 2013).…”
Section: Background Information On Studymentioning
confidence: 99%